Parents' intention toward early marriage of their adolescent girls in eastern Ethiopia: A community-based cross-sectional study from a social norms perspective - Abdurahman, Dureti; Assefa, Nega; Berhane, Yemane (Frontiers in Global Women's Health, 2022)
Background: Strong social norms around early marriage put pressure on parents to marry off their adolescent girls at an early age. Early marriage is widely practiced in many parts of Ethiopia. However, early marriage studies rarely address the role of social norms. This study aim to examine the role of social norms on parents’ intention to early marry adolescent girls in Eastern Ethiopia. Method: A community-based cross-sectional study was conducted during September to November 2019. A multistage sampling procedure was applied to select the study participants. Factors related to parent’s intention to early marriage were assessed through a lens of Theory of Planned Behavior. Adjusted Prevalence Ratio (PR) was calculated using a log-binomial model to identify factors associated with intention to early marriage. Results: A total of 859 mothers and 859 fathers of unmarried girls were included in the study. The prevalence of intention to marry off their daughter early among mothers was 39.70% (95% CI=36.4%-43.0%) and 43.54% (95%CI=40.2%–47.1%) among fathers of adolescent girls (chi2 (1) =41.8; P < 0.001). The intention for an early marriage was higher among mothers and fathers with favorable attitude towards early marriage, in those who believe that most people in their reference group conform to early marriage norms (empirical expectation), in those who believe that most people in their reference group expect them to conform to early marriage norms (normative expectation) and among fathers who did not know the legal age of marriage for adolescent girls and those who did not know the health consequences of early marriage. The prevalence of intention to early marriage was lower among mothers (APR=0.49; 95% CI: 0.36-0.65) and fathers (APR= 0.62; 95% CI: 0.49-0.78) in urban areas; and among mothers (APR=0.41; 95% CI: 0.27-0.62) and fathers (APR=0.50; 95% CI: 0.38-0.67) with higher educational level. Conclusion: The social norms that promote intention for an early marriage is still high among parents, especially in those living in rural areas and uneducated parents. Hence, interventions that aims to reduce early marriage need to address locally relevant social norms.